The Association between Gender, Perceived Burdensomeness, and Suicidal Ideation Among Junior High School Students in the Philippines - Herrera, Joebren S. (Indonesian Psychological Research, 2026)
This study examined the association between gender, perceived burdensomeness (PB), and suicidal ideation (SIQ) among Junior High School students in the Philippines, addressing the limited local data on these variables, particularly in rural settings. A descriptive-correlational quantitative research design was employed with a sample of 285 junior high school students.  Data were collected using the Interpersonal Needs Questionnaire (INQ-15) and the Suicidal Ideation Questionnaire (SIQ). The results showed significant gender differences in both perceived burdensomeness and suicidal ideation, with female and male students reporting different levels on these measures. A moderately positive association was observed between PB and SIQ scores, indicating that higher perceived burdensomeness is linked to higher suicidal ideation. Regression analysis further revealed that for every one-unit increase in PB, SIQ scores increased by approximately 1.93 points on average (B = 1.93, SE = 0.23, t = 8.29, p < .001). These findings highlight perceived burdensomeness as a critical risk factor for suicidal ideation among junior high school students in the Philippines. The findings also suggest that suicidal ideation expression may vary according to gender and individual psychological factors.